2010
DOI: 10.1016/j.jml.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The associative structure of language: Contextual diversity in early word learning

Abstract: Previous studies demonstrated that statistical properties of adult generated free associates predict the order of early noun learning. We investigate an explanation for this phenomenon that we call the associative structure of language: early word learning may be driven in part by contextual diversity in the learning environment, with contextual diversity in caregiver speech correlating with the cue-target structure in adult free association norms. To test this, we examined the co-occurrence of words in caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
288
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(319 citation statements)
references
References 87 publications
(116 reference statements)
25
288
3
3
Order By: Relevance
“…the negative definition), and the consistency needed to facilitate appropriate word usage in early language learners. Prior work investigating the statistical structure of child-directed language corpora found that diversity in word cooccurrence was a predictor of order of acquisition of children's earliest learned words (Hills et al, 2010). Words embedded in more linguistically diverse speech were learned earlier.…”
Section: University Of Warwickmentioning
confidence: 99%
See 4 more Smart Citations
“…the negative definition), and the consistency needed to facilitate appropriate word usage in early language learners. Prior work investigating the statistical structure of child-directed language corpora found that diversity in word cooccurrence was a predictor of order of acquisition of children's earliest learned words (Hills et al, 2010). Words embedded in more linguistically diverse speech were learned earlier.…”
Section: University Of Warwickmentioning
confidence: 99%
“…This structure is evaluated with respect to statistics traditionally associated with language acquisition (frequency and word repetitions) as well as attributes that may contribute to acquiring the meaning of children's earliest learned words, specifically ASSOCIATIVE STRUCTURE and CONTEXTUAL DIVERSITY (e.g. Hills, Maouene, Riordan & Smith, 2010). Associative structure is a measure of how often a word appears near its associates (as measured by adult free association norms ; see below) in natural language.…”
Section: University Of Warwickmentioning
confidence: 99%
See 3 more Smart Citations